PENGARUH KOREKSI BENTUK MATA SIPIT PADA RIAS PENGANTIN BARAT - Mandalika, Mandalika; Hayatunnufus, Hayatunnufus; Yanita, Merita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The shape of narrow eyes generally makes the owner feel unconfident about the shape of her eyes. To make eye shape look proportional then needed some correction of eye shape using eyeliner, scotch tape, and false eyelashes to form eye to look proportional and make the bride more confident and to make the makeup look good at the day. This research aims to analyze the influence of correction the shape of narrow eyes on bridal makeup to predefined university students assessed in terms of, eye size, eyelid crease, and eyelash shape.This research uses quasi experimental method with design (non Equivalent Control Group Design) The object of this study is the shape of narrow eyes. The population in this study is the student of Padang State University aged 18-22 years, have the same criteria, the sampling taken through Purposive Samplingg technique conducted in voolunteer with sampels of 3 people. The data collected from this research in the form of primary data obtained directly from the sample of research data collected were analyzed using descriptive analysis, the test of analysis requirements using Normality Test and Homogeneity Test, Test Analysis of Variance (ANAVA) and Duncan Test.Based on the results of the data, proving the correction of the form of narrow eyes on the bridal makeup without using eyeliner, scotch tape, and false eyelashes in the control group did not show a better result change for experimental group using eyeliner and scotch tape. Using eyeliner, scotch tape, and false eyelashes showed significant results on eye size, eyelid folds, and eyelashes. Differences in the effect of spiky eye correction on bridal makeup between leagues treated group showed significant result with Î± 0,000, because 0,000 < 0,050 then the hypothesis is accepted and then proceed with Duncan test showing significantly different group. Suggested of using eyeliner, scotch tape, and false eyelashes in the correction of the shape of narrow eyes to make the makeup more perfect.Keyword : The Shape of Narrow Eyes, Bridal Makeup3